O casamento na infância e adolescência no Brasil: as principais camadas e desafios enfrentados na redução de casos, a partir de uma análise pós-colonial - Prates, Andressa Camargo (2024)
The work “Child and adolescent marriage in Brazil: the main layers and challenges faced in case reduction, from a postcolonial analysis” by Andressa Prates offers a postcolonial analysis of child and adolescent marriage practices in Brazil, based on a bibliographic review methodology of the main reports and studies on this topic in the country and worldwide. This study also examines the main challenges the country faces in achieving better results in reducing these cases, through the lens of four categories selected from postcolonial literature (Voice and Silence, Intersectionality, Culture and the maintenance of customs and social structures, and Systems and binary simplifications). By conducting a multidisciplinary analysis of the practice, it allows a broader understanding of it. Brazil currently ranks 6th in terms of the absolute number of marriages involving at least one spouse under 18 years old (UNICEF, 2023a). Unlike other countries, in Brazil, as well as in Latin America and the Caribbean, girls have greater agency in the decision to marry (TAYLOR et al., 2015, p.9). Despite of a “choice”, this practice is a violation of human rights and a failure of the Doctrine of Integral Protection for children and adolescents in Brazil, what means that if the rights of this population were being guaranteed, this type of marriage would not be considered a viable or less harmful option compared to other situations they experience. In the country, there are still no reliable data surveys on this theme, which is significantly exacerbated by the informal nature of these unions, what hinders a complete understanding of the matter, as well as the influence it exerts and undergoes in relation to other intersecting topics (such as child and/or adolescent pregnancy, school dropout, female poverty, domestic violence, among others). Finally, the main themes explored include: 1) Children’s rights and legislation; 2) Data collection; 3) Intersection of child and adolescent marriage with other topics; 4) Agency of girls; 5) Transversalization of gender in public policies. Regarding the main challenges the country faces in achieving better results in reducing these cases are: 1) Failures in guaranteeing the rights of children and adolescents; 2) Lack of official surveys on child and adolescent marriage in Brazil; 3) The complexity of the topic due to its interdisciplinary nature and intersections with other issues; 4) Lack of attention to the Brazilian reality by International Institutions; 5) Strong presence of harmful practices for girls that lead to child and adolescent marriage; 6) Lack of knowledge about the topic among legislators and competent bodies responsible for protecting this population; 7) Privatization and silencing of women’s realities in the country, hindering them from sharing experiences of violence that could help other women